Mortality and Disability According to Baseline Blood Pressure in Acute Ischemic Stroke Patients Treated by Thrombectomy: A Collaborative Pooled Analysis. Issue 10 (10th October 2017) - Maïer, Benjamin; Gory, Benjamin; Taylor, Guillaume; Labreuche, Julien; Blanc, Raphaël; Obadia, Michael; Abrivard, Marie; Smajda, Stanislas; Desilles, Jean‐Philippe; Redjem, Hocine; Ciccio, Gabriele; Lukaszewicz, Anne Claire; et al.
Abstract : Background: High blood pressure (BP) is associated with worse clinical outcomes in the setting of acute ischemic stroke, but the optimal blood pressure target is still a matter of debate. We aimed to study the association between baseline BP and mortality in acute ischemic stroke patients treated by mechanical thrombectomy. Methods and Results: A total of 1332 acute ischemic stroke patients treated by mechanical thrombectomy were enrolled (from January 2012 to June 2016) in the ETIS (Endovascular Treatment in Ischemic Stroke) registry. Linear and polynomial logistic regression models were used to assess the association between BP and mortality and functional outcome at 90 days. Highest mortality was found at lower and higher baseline systolic blood pressure (SBP) values following a J‐ or U‐shaped relationship, with a nadir at 157 mm Hg (95% confidence interval 143‐170). When SBP values were categorized in 10–mm Hg increments, the odds ratio for all‐cause mortality was 3.78 (95% confidence interval 1.50‐9.55) for SBP<110 mm Hg and 1.81 (95% confidence interval 1.01‐3.36) for SBP≥180 mm Hg using SBP≥150 to 160 mm Hg as reference. The rate of favorable outcome was the highest at low SBP values and lowest at high SBP values, with a nonlinear relationship; in unplanned exploratory analysis, an optimal threshold SBP≥177 mm Hg was found to predict unfavorable outcome (adjusted odds ratio 0.47; 95% confidence interval 0.31‐0.70). Conclusion: In acute ischemic stroke patients treated by mechanical thrombectomy, baseline SBP is associated with all‐cause mortality and favorable outcome. In contrast to mortality, favorable outcome rate was the highest at low SBP values and lowest at high SBP values. Further studies are warranted to confirm these findings.